Microsensors Based on MEMS Technology - Gupt, Amita; Ahmad, Amir (Defence Science Journal, 2007)
Sensors play an important role in most of the common activities that occur in our daily lives. They are the building blocks of or microelectromechanical systems (MEMS). This combination of micromechanical structures, sensing elements, and signal conditioning is the beginning of a new era in sensor technology. Sensing systems incorporated with dedicated signal processing functions are called intelligent sensors or smart sensors. The present decade of new millennium will be the decade of smart systems or MEMS. The rapid rise of silicon MEMS recently was due to major advances in silicon microfabrication technology, especially surface micromachining, deep-reactive ion etching, and CMOS-integrated MEMS. In this paper, an overview of the currently available MEMS sensors, materials for sensors and their processing technologies, together with integraticm of sensors and electronics is presented.